PENGEMBANGAN MATA KULIAH APRESIASI DAN KAJIAN DRAMA BERBASIS KEBUDAYAAN BREBES SEBAGAI BAHAN AJAR MAHASISWA - Ghufroni (Sasando, 2020)
Teaching material as a course development is a teaching material that is packaged as material to be presentedinthelearningprocess.Thentheteachingmaterialsmustbemadesointerestingthatstudents aremoreenthusiasticinlecturing.Thatisthereasonwhylecturersintertiaryinstitutionsmustdevelop course teaching materials, one of which is the Appreciation and Drama Study course by integrating Brebes culture with the aim of gaining drama knowledge as well as raising awareness of the spirit of preserving its own culture. The purpose of this research is to compile the development of the Brebes Culture-basedAppreciationandDramaStudycourseandtotesttheeffectivenessofteachingmaterials. This research uses the research and development (R & D) method with the research steps, namely 1) Literature study, 2) Research planning, and 3) Implementation of the final product. The results of this studyarelearningbooksthatmeettheneedsofstudentsandlecturers,aswellasmeetingtheprinciples ofdevelopinglearningbooks.Basedontheresultsoftheeffectivenesstest,thisAppreciationandDrama Study course book is effectively used in learning for students of Indonesian language and literature education at Muhadi SetiabudiUniversity.